DEVELOPMENT OF THE SOCIAL SECTOR OF KASHKADARYA REGION - Jorayeva Elenora Kahramon kizi (Western European Studies, 2025)
This scientific article provides an in-depth analysis and commentary on how the social sphere has developed in the Kashkadarya region since the years of independence. The article details the reforms implemented in the region in areas such as social infrastructure, education, healthcare, culture and sports and their impact on the lives of the population. It also examines the role of state policy in the development of the social sphere and the strategies used in this regard, as well as their results. The article analyzes how social policies have been implemented in the region and what achievements have been achieved through these policies.
Keywords: Kashkadarya region; years of independence